4-Hydroxy-trans-cinnamate Derivatives and Triterpene from Barleria cristata (Dhaka University Journal of Pharmaceutical Sciences, 2014)
Barleria cristata is an important medicinal plant of Bangladesh. Many compounds of diverse biological activities were isolated from different Barleria species, including irridoids, flavonoids and phenylethanoid derivatives in addition to other groups of chemical constituents. This paper presents the chemical investigation of the whole plants of B.cristata. Classic phytochemical investigation of organic extracts of the whole plants of B. cristata together with spectroscopic methods led to the isolation and characterization of 4-hydroxy-trans-cinnamate derivatives (1-3) and a triterpene, namely oleanolic acid (4). Dhaka Univ. J. Pharm. Sci. 12(2): 143-145, 2013 (December) DOI: http://dx.doi.org/10.3329/dujps.v12i2.17623